Selective vulnerabilities of N-methyl-D-aspartate (NMDA) receptors during brain aging - Magnusson, Kathy R.; Brim, Brenna L.; Das, Siba R. (Frontiers in Aging Neuroscience, 2010)
N-methyl-D-aspartate (NMDA) receptors are present in high density within the cerebral cortex and hippocampus and play an important role in learning and memory. NMDA receptors are negatively affected by aging, but these effects are not uniform in many different ways. This review discusses the selective age-related vulnerabilities of different binding sites of the NMDA receptor complex, different subunits that comprise the complex, and the expression and functions of the receptor within different brain regions. Spatial reference, passive avoidance, and working memory, as well as place field stability and expansion all involve NMDA receptors. Aged animals show deficiencies in these functions, as compared to young, and some studies have identified an association between age-associated changes in the expression of NMDA receptors and poor memory performance. A number of diet and drug interventions have shown potential for reversing or slowing the effects of aging on the NMDA receptor. On the other hand, there is mounting evidence that the NMDA receptors that remain within aged individuals are not always associated with good cognitive functioning. This may be due to a compensatory response of neurons to the decline in NMDA receptor expression or a change in the subunit composition of the remaining receptors. These studies suggest that developing treatments that are aimed at preventing or reversing the effects of aging on the NMDA receptor may aid in ameliorating the memory declines that are associated with aging. However, we need to be mindful of the possibility that there may also be negative consequences in aged individuals.